Perception of community medicine as a curriculum and career option among medical students - Muthamilan, Om Lokesh; Hapani, Pragati Amit; Beotra, Sakshi; Kotian, Shashidar; Goyal, Ishan (International Journal Of Community Medicine And Public Health, 2022)
Background: In India, medical curricula have not been kept up to date with changes in public health, demography, and health policies. Clinicians serve as role models for students in medical colleges, and CM is not seen as an appealing career option by students. Hence this study was designed to analyze the perceptions and attitudes of medical undergraduates towards the relevance of CM as a future career option. Methods: This cross-sectional study was done in a Kasturba medical college, Manipal academy of higher education, located in Mangaluru, conducted especially for undergraduate medical students consisting of 440 medical students (MS) formulate this study population who belonged to different socio-demographic and regional backgrounds. Results: This study on the perceptions of the MS in LCM as part of their MBBS syllabus and their preference for the subject as a career path. Out of 440 MS, the rate of response was 100%. Among them, 237 (53.8%) were male and 203 (46.2%) were female. In our study, 93.9% showed a positive attitude in gaining skills to understand the research in their period of CM postings, 89.7% suggested having an understanding of concepts in CM followed by preventive measures against diseases (86.6%), the real-life health issues of the community Conclusions: The prime motive was a desire to pursue a career in clinical subjects, students must learn community medicine subjects as well, and they must be better informed about the chances were available for CM specialists to work with international, national and state healthcare organisations and research institutes.